Envelhecimento humano e contemporaneidade : reflexões sobre a questão de acessibilidade - Bordignon, Karim Kaiomi de Oliveira (2014)
Population aging and urbanization configured into two global trends that, together, represent the major forces shaping the twenty-first century. At the same time as cities grow, grows, growing, its population group aged 60 years or more, the main current problems, rapid transfiguration of urban scenarios in the name of progress, requiring elderly flexibility to position before the new.View of this reality, it was aim to investigate if the elderly recognize elements of accessibility in public urban areas, and if these areas are accessible in relation to population aging. This is a cross-sectional qualitative descriptive approach with semistructured interviews. The study included 83 patients of both sexes, with 48 participants from urban area and 35 from rural areas accounting for 20% of elderly regulars in social groups in Frederico Westphalen - RS.From the presentation of a video about accessibility and explanation on the topic was held data collection groups through individual interviews with semi-structured questionnaire of questions, analyzed qualitatively the data using content analysis and interpretation follows the light of referential constructed on accessibility and aging. On the issue of accessibility, most participants did not know what the word meant and nor what it comprises.A very important aspect mentioned by respondents was the lack of education of society towards oldest. Among the results that were recorded for analysis and interpretation of data, the most frequently mentioned topic by seniors about the difficulties in access to urban public areas was the lack of public transport, then problems as: obstacles on sidewalks, difficulties and fear for cross the road and lack of parking reserved for seniors.With the experience of the elderly as the protagonist of his story, expressing their wishes and needs that characterize their demands in relation to accessibility, certainly contribute to compatible environment with aging from an interdisciplinary view, seeking active aging and quality of life we desire